Teaching with Visual Narratives: A Practical Usage of English Language - Chattopadhyay, Pallabi; Subedi, Abhi; Sharma , Sagar (Bodhi: An Interdisciplinary Journal, 2025)
An increasing curiosity in communication through visual narratives has been observed in recent years in multidisciplinary research. This paper is based on my own experience in the classroom about how English grammar is taught with the help of visual narratives. This teaching method can be considered an exclusive way of teaching grammar in context through the strategic fusion of language and literature rather than treating them as two separate entities of the English language. The linguistic sequential nature of comic strips or visual narratives displays an excellent source of teaching materials that would allow teachers and students to find novel approaches to language in an intriguing and creative way. With the help of a descriptive research method, this paper shows how to practice the formation of different word classes with the different tense forms and usage of modals through certain selected visual narratives.